Heinrich event 1: an example of dynamical ice-sheet reaction to oceanic changes - Álvarez Solas, Jorge; Montoya Redondo, María Luisa; Ritz, C.; Ramstein, G.; Charbit, S.; Dumas, C.; Nisancioglu, K.; Dokken, T.; Ganopolski, A. (Copernicus Gesellschaft MBH, 2011)
We thank Y. Donnadieu, D. Paillard, D. Roche, F. Remy, F. Pattyn, A. Robinson and E. Lucio for helpful discussions, and two anonymous referees and the editor Andre Paul who helped to improve the manuscript. Figure 5 of this article is based on a similar figure suggested by referee #2. We are also greatful to the PalMA group for useful comments and suggestions. This work was funded under the MOVAC and SPECT-MORE projects. J. A-S was also funded by the Spanish programme of the International Campus of Excellence (CEI). Heinrich events, identified as enhanced ice-rafted detritus (IRD) in North Atlantic deep sea sediments (Heinrich, 1988; Hemming, 2004) have classically been attributed to Laurentide ice-sheet (LIS) instabilities (MacAyeal, 1993; Calov et al., 2002; Hulbe et al., 2004) and assumed to lead to important disruptions of the Atlantic meridional overturning circulation (AMOC) and North Atlantic deep water (NADW) formation. However, recent paleoclimate data have revealed that most of these events probably occurred after the AMOC had already slowed down or/and NADW largely collapsed, within about a thousand years (Hall et al., 2006; Hemming, 2004; Jonkers et al., 2010; Roche et al., 2004), implying that the initial AMOC reduction could not have been caused by the Heinrich events themselves. Here we propose an alternative driving mechanism, specifically for Heinrich event 1 (H1; 18 to 15 ka BP), by which North Atlantic ocean circulation changes are found to have strong impacts on LIS dynamics. By combining simulations with a coupled climate model and a three-dimensional ice sheet model, our study illustrates how reduced NADW and AMOC weakening lead to a subsurface warming in the Nordic and Labrador Seas resulting in rapid melting of the Hudson Strait and Labrador ice shelves. Lack of buttressing by the ice shelves implies a substantial ice-stream acceleration, enhanced ice-discharge and sea level rise, with peak values 500-1500 yr after the initial AMOC reduction. Our scenario modifies the previous paradigm ...